Four rationales of HE internationalisation: perspectives of UK universities on attracting students from former Soviet countries - Chankseliani, M (SAGE Publications, 2017)
In the context marked by increasing competition between nation-states and universities, expanding individualisation, growing influence of non-state actors, and the new reality of Brexit, his study uses narrative and numeric data to explore the rationales of UK higher education internationalisation, specifically motives of attracting students from Eastern Europe, Russia, Caucasus, and Central Asia to the UK. Amongst four main rationales of international student recruitment, economic rationale emerged as the most decisive. Interviewees viewed student mobility from this region as an expression of socio-economic transformation in sending countries as well as political and strategic priorities in the UK. They referred to the economic situation in the region, the development of the HE sector within the source countries, the UK government discourse on migration, and universities’ own strategic planning as four main issues that can influence future trends of student mobility from this region to the UK.